Kapasitas Berinovasi Penyelenggaraan Desa - Utomo, Diajeng Intan Putri; Wardhani, Nuruni Ika Kusuma (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2025)
The capacity for innovation in village governance reflects efforts to bridge community welfare and social transformation. This study examines innovation from both institutional and community perspectives, emphasizing the role of social and grassroots innovation in empowering village apparatus and local communities. Employing a qualitative case study approach, the research focuses on two villages in Lamongan Regency: Warukulon and Wanar. Data were collected through interviews with village officials, community-based organizations (LKD), and local service units such as posyandu. The findings indicate that institutional innovation capacity remains limited, as training and development for village officials are irregular and highly dependent on external directives. Conversely, innovation at the grassroots level, particularly through Karang Taruna, PKK, and posyandu, has shown promise in community mobilization and empowerment. Warukulon demonstrates relatively higher community innovation due to active participation since the COVID-19 pandemic, while Wanar is in the early stages of revitalizing youth engagement. This research highlights the need for sustainable training programs, institutional support, and leadership regeneration to strengthen local innovation ecosystems. These findings underline the importance of integrating both top-down and bottom-up approaches in enhancing village innovation capacity.